(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
This paper discusses the results of a study on formula instruction conducted among mixed-ability diploma level university students. The main objective of the study was to investigate whether incorporating direct instruction of academic formulas (DIAF) into an academic writing class would encourage the use of the target academic formulas (TAF) in the post academic essay writing (AEW) test, and improve the subjects academic writing performance. Two intact groups of diploma level university students enrolled in an academic writing course employing a process-oriented writing approach participated in the study. Both groups consisted of forty students and were assigned as the experimental and control groups. DIAF was incorporated into the existing academic writing courses syllabus and was conducted two hours per week over six out of the fourteen-week semester. Pre and post AEW tests were used to assess the subjects academic writing performance before and after the treatment. The results of the study are discussed by addressing three research questions: 1) What are the effects of DIAF on the TAF use in the post AEW test? 2) What is the effect of TAF use on the post AEW test scores? 3) What are the effects of DIAF on the subjects academic writing performance? It was concluded that DIAF encourages the use of more TAF and a more varied selection of TAF in the post AEW test. There is a significant but weak positive linear relationship between the number of TAF used in the post AEW test and the post AEW test scores (r=0.473), and the number of TAF used is a significant predictor in estimating the scores for all the three AEW test components. DIAF is also beneficial at enhancing the subjects academic writing performance with a large effect size of 0.98 for language component, 0.86 for organization component and a small effect size of 0.45 for content component.